A terrorizmus elleni védekezés - Kovács, Krisztina (Debreceni Jogi Műhely, 2005)
In the last decades of our globalized world terrorism has become a phenomenon that implies a worldwide challenge and can hardly be prevented, and that is difficult to combat against with means of national and international law. The international terrorism in the sense as we use it nowdays has a history of only one and a half centuries, but since the appearance of concrete terrorist attacks is always changing (and of course the ideology and supplier of the different groups) there has not been any consensus yet among states or within particular international organizations how to define it. But it should be taken into consideration that attacks not only affect the state where they are executed but also the whole society and even the international order. That is why it would be essential to define it in international terms, because without an exact definition the proper defence against it can not be determined either. It has to be emphasized that it does not exist a common strategy that could be adapted any time in any case. It can not be forgotten that the terrorism itself is also an answer, so its political, economical and social roots should be taken into consideration whilst choosing the best way to prevent it. The different means (primarily legal and classical ones) should be combined and used by states in strict cooperation, because these don’t substitute but complete each other. It is also important to underline that it is not enough to react upon terrorist actions and restore its harmful effects, but it is also essential to prevent it by eliminating its causes. Unfortunately, proactive strategies are not common enough - mainly because of its costs - in spite of the fact that in the long run it would be worth using them. It is important to act in conformity with international law, because this can legitimate the reaction after an attack. The main task for states is to elaborate an exact legal framework for it, because without global accords and without the acceptance of this policy within the nation an effective policy against terrorism cannot be realized. National criminal law should be aggravated, flow of information among intelligence services, cooperation among media and governments should be developed and it is also essential to inform the society properly and make it obvious that assistance at a terrorist attack is also to be punished. International measures should be taken in order to avoid financing of terrorist actions by preventing money-laundering. These means can be used even with certain restrictions on criminal law, but always respecting human rights either that of the victims or that of the delinquents. To institutionalize international actions under the aegis of the United Nations numerous agreements were accepted, eg. Convention on the Prevention and Punishment of Crimes against Internationally Protected Persons (1973), Convention against Taking of Hostages (1979), Convention for the Suppression of the Financing of Terrorism (1999) and some conventions were signed on the Prevention Crimes committed in aircrafts, etc. The main problem is that these accords are not signed by all member states and hence their efficiency can be questioned. Of course not only the UN try to solve this problem with international conventions, so does the EU. Its activity has considerably increased since the attacks of Madrid, because this case made two things clear: even Europe is vulnerable and well-timed attacks can even lead to political changes. To be able to meet the challenges that terrorism mean nowdays there are two things to emphasize: first of all a worldwide cooperation would be essential and secondly the provision of financial sources for each state so that it were able to ensure national and promote global security.